Students’ Public Speaking Assessment for Informative Speech - Pipit Rahayu; Yenni Rozimela; Jufrizal Jufrizal (AL-ISHLAH: Jurnal Pendidikan, 2022)
Public Speaking is considered as an essential skill for University Students. Public speaking is having a speaker stand before the audience to deliver a speech in a structured manner, to either persuade, inform, or entertain the audience.This study aimed to reveal the extent of students’ skills in public speaking skill especially for persuasive and informative speech. This research was descriptive quantitative. Data were obtained from students' public speaking test of 58 English studentsat English Department University of Pasir Pengaraian and analyzed and described in qualitatively. The finding came up with encouraging numbers of results where a greater proportion of the samples reported significant number in good level of categories in assessing public speaking skill. More over, the result showed that the highest score of students’ in public speaking skill was in vocabularies and comprehension. Besides, it was indicated that the students gradually could express their thought and opinions smoothly in informative speech then persuasive speech.